Powdery hydraulic composition

JP2023184239A5Active Publication Date: 2025-03-18KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022098279
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-17
Publication Date
2025-03-18
Estimated Expiration
2042-06-17

AI Technical Summary

Technical Problem

Existing hydraulic compositions in powder form face challenges with decreased strength and poor handling due to the use of powdered alkali compounds like metasilicate hydrate, which impairs fluidity and handling properties.

Method used

A coated fine aggregate with an inorganic binder layer containing metasilicate hydrate on its surface and alumina-silica fine powder is used, enhancing handling properties and strength development by improving fluidity and contact surface area during curing.

Benefits of technology

The solution provides a powdery hydraulic composition with excellent handling properties and strong cured products, contributing to sustainable development goals by utilizing industrial by-products and reducing emissions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a powdery hydraulic composition that has superior handleability, and yields a cured body with superior strength.SOLUTION: A powdery hydraulic composition contains (A) coated fine aggregate that includes fine aggregate and an inorganic binder layer, formed on the surface of the fine aggregate and containing metasilicate hydrate and (B) alumina silica fine powder.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powdery hydraulic composition, a hydraulic slurry, a method for producing a powdery hydraulic composition, and a method for producing a hardened body.

Background Art

[0002] In recent years, for the realization of SDGs, infrastructure development considering the environment from the ESG perspective has been aimed at, and technological development of an environmentally friendly hydraulic composition with reduced cement that emits CO2 during the calcination of calcium carbonate has been progressing.

[0003] As an example, a hydraulic composition called geopolymers that hardens blast furnace slag fine powder containing silicates such as aluminum silicate using an alkaline solution has attracted attention.

[0004] Patent Document 1 discloses a geopolymer composition using a filler, an alkali activator, and an aggregate as raw materials. Patent Document 2 includes blast furnace slag fine powder and fly ash as powder raw materials, fine aggregate, silica fume, potassium hydroxide or sodium hydroxide as an alkali source, and water, and the volume ratio of the powder raw material of blast furnace slag fine powder: BFS / P is 35 to 80%, and the molar ratio of silicon contained in silica fume to the alkali source: Si / A is 0.05 to 0.35, and the molar ratio of the alkali source to water: A / W is 0.1 to 0.3, and a geopolymer composition is disclosed.

[0005] Non-Patent Document 1 discloses the definition, materials, mechanism, problems, and possibilities of geopolymers. Non-Patent Document 2 discloses a one-component type geopolymer composed of alumina-silica fine powder, a powdery alkali compound, and an aggregate without using an alkaline solution.

Prior Art Documents

Patent Documents

[0006] [Patent Document 1] Japanese Patent Publication No. 2008-239446 [Patent Document 2] Japanese Patent Publication No. 2021-66613 [Non-patent literature]

[0007] [Non-Patent Document 1] Concrete Engineering, Vol. 56, No. 5, pp. 409-414, The Japan Concrete Institute, published May 2018. [Non-Patent Document 2] Cement and Concrete Research, Vol. 103, pp. 21-34, Elsevier BV, November 2017. [Overview of the project] [Problems that the invention aims to solve]

[0008] If hydraulic compositions for geopolymers can be obtained in powder form, flexibility in terms of handling and other aspects can be improved. For this purpose, it is desirable that the compounding raw materials, such as alkali compounds, also be in powder form. However, when metasilicate hydrate is incorporated as a powdered alkali compound, there are challenges such as a decrease in the strength of the hardened product compared to when it is added as an aqueous solution, and impaired handling due to the low fluidity of the powdered metasilicate hydrate. The present invention provides a powdered hydraulic composition that exhibits excellent handling properties and good strength in its cured form. [Means for solving the problem]

[0009] The present invention relates to a powdered hydraulic composition comprising (A) a coated fine aggregate having a layer of fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate [hereinafter referred to as component (A)], and (B) alumina silica fine powder [hereinafter referred to as component (B)].

[0010] Furthermore, the present invention includes a step (1) of mixing metasilicate hydrate and fine aggregate at a temperature above the melting point of the metasilicate hydrate to obtain a mixture, Step (2) is to cool the mixture to a temperature below the melting point of the metasilicate hydrate to obtain a coated fine aggregate having (A) fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate [hereinafter referred to as component (A)], (A) A step (3) of mixing component (A) and (B) alumina silica fine powder, This invention relates to a method for producing a powdered hydraulic composition containing [a specific substance].

[0011] Furthermore, the present invention relates to a hydraulic slurry obtained by compounding the powdered hydraulic composition of the present invention with water.

[0012] Furthermore, the present invention includes a step (I) of mixing the powdered hydraulic composition of the present invention with water to obtain a hydraulic slurry, (II) A step of curing the hydraulic slurry to obtain a hardened body, This relates to a method for producing a cured body, including the following:

[0013] Furthermore, the present invention relates to an additive for powdered hydraulic compositions, comprising a coated fine aggregate having a fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate. [Effects of the Invention]

[0014] According to the present invention, a powdered hydraulic composition is provided that exhibits excellent handling properties and good strength in its cured form. Because this invention contributes to the effective utilization of industrial by-products and waste, and to the reduction of CO2 emissions, it is considered that this technology could contribute to SDGs such as No. 7, 9, 11, 12, and 13, which have been advocated in recent years for the realization of a sustainable society. [Modes for carrying out the invention]

[0015] The inventors have found that by combining component (A) and component (B), the handling property of a powdery hydraulic composition of a single dosage form is improved, and the strength development property when a hydraulic slurry prepared from such a powdery hydraulic composition is used as a hardened body is improved. Although the reason for the manifestation of such an effect is not necessarily clear, it is presumed as follows. (A) The fine aggregate used in the component generally has a porous structure mainly composed of a silicate compound. However, gas (air, water vapor) exists in the porous structure, and it is considered that the infiltration of the inorganic binder into the porous structure is limited due to the surface tension of the inorganic binder and the air pressure in the porous structure. In the present invention, in the process of forming an inorganic binder layer containing metasilicate hydrate on the fine aggregate having a porous structure, the inorganic binder containing metasilicate hydrate infiltrates into the porous structure, thereby improving the fluidity of the powder, increasing the contact surface area between the inorganic binder and the fine aggregate, and making the inorganic binder and the fine aggregate more firmly bonded in the curing process, thus improving the strength development property of the hardened body. In addition, the alumina-silica fine powder of component (B) tends to aggregate by interparticle forces such as liquid cross-linking force with metasilicate hydrate and impair the fluidity of the powder. However, due to the infiltration of the inorganic binder into the fine aggregate used in the above component (A), the contact area between the metasilicate hydrate and the alumina-silica fine powder is reduced, and the decrease in the fluidity of the powder is suppressed, and good fluidity is obtained. When preparing a hydraulic slurry by adding water to the powdery hydraulic composition of the present invention, since the metasilicate hydrate infiltrated into the fine aggregate used in the above component (A) quickly dissolves in water, the reaction with the alumina-silica fine powder of component (B) also proceeds smoothly, which is considered to contribute to the development of the hardened body strength. Note that the mechanism of action of the present invention is not limited to this.

[0016] <Powdery hydraulic composition> The powdery hydraulic composition of the present invention contains a predetermined coated fine aggregate of component (A) and an alumina-silica fine powder of component (B).

[0017] (A) Component comprises fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate.

[0018] The angle of repose of component (A) is preferably 35° or less from the viewpoint of the handling properties of the powdered hydraulic composition. The angle of repose of component (A) is measured using the angle of repose measuring instrument ASK-01 (manufactured by AS ONE Corporation).

[0019] From the viewpoint of improving the handling properties of the powdered hydraulic composition and the workability of the hydraulic slurry, it is preferable that component (A) is spherical. Here, in this embodiment, component (A) is spherical, meaning it has a round shape like a ball, and more specifically, it has a sphericity of preferably 0.80 or higher, more preferably 0.85 or higher, even more preferably 0.90 or higher, even more preferably 0.95 or higher, and even more preferably 0.97 or higher. It is preferable from the viewpoint of the workability of the hydraulic slurry that the sphericity of component (A) in this embodiment is equal to or higher than the above lower limit. Furthermore, the upper limit for sphericity is specifically 1 or less.

[0020] (A) The sphericity of component (A) is determined by image analysis of the particle image (photograph) obtained using an optical microscope or digital scope (e.g., Keyence VH-8000), thereby determining the area of ​​the particle projection cross-section and the perimeter of said cross-section, and then [Area of ​​particle projection cross-section (mm²)] 2 The value can be calculated by dividing the circumference of a perfect circle with the same area (mm) by the perimeter of the particle projection cross-section (mm), and then averaging the obtained values ​​for any 50 particles.

[0021] (A) The average particle size of component (A) is preferably 0.1 mm or more, more preferably 0.5 mm or more, and more preferably 5.0 mm or less, more preferably 2.0 mm or less, and even more preferably 1.0 mm or less, from the viewpoint of handling the powdered hydraulic composition. In this embodiment, the average particle size of component (A) can be measured by the following method.

[0022] (Method for measuring average particle size) If the sphericity of the particle from the particle projection cross section is 1, the diameter (mm) is measured. On the other hand, if the sphericity is < 1, the major axis diameter (mm) and minor axis diameter (mm) of randomly oriented particles are measured, and (major axis diameter + minor axis diameter) / 2 is calculated. For any 100 particles, the obtained values ​​are averaged to obtain the average particle size (mm). The major axis diameter and minor axis diameter are defined as follows: When a particle is stabilized on a plane and its projection image onto the plane is sandwiched between two parallel lines, the width of the particle at which the distance between the parallel lines is minimized is called the minor axis diameter. On the other hand, the distance when the particle is sandwiched between two parallel lines perpendicular to these parallel lines is called the major axis diameter. The major and minor axis diameters of a particle can be determined by taking an image (photograph) of the particle using an optical microscope or digital scope (for example, Keyence VH-8000 model) and performing image analysis on the obtained image.

[0023] (A) The fine aggregate used in component (A) may be natural sand or artificial sand. Examples of natural sand include river sand, land sand, mountain sand, sea sand, limestone sand, silica sand, chromite sand, zircon sand, olivine sand, alumina sand, natural lightweight fine aggregate, and crushed versions thereof. Examples of artificial sand include blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, recycled fine aggregate, synthetic mullite sand, SiO2-based artificial sand with SiO2 as the main component, Al2O3-based artificial sand with Al2O3 as the main component, SiO2 / Al2O3-based artificial sand, SiO2 / MgO-based artificial sand, SiO2 / Al2O3 / ZrO2-based artificial sand, and SiO2 / Al2O3 / Fe2O3-based artificial sand. Here, the main component refers to the most abundant component in the sand. These can be used individually, or two or more can be used in combination.

[0024] From the viewpoint of the workability of the hydraulic slurry, the degree of amorphousness of the fine aggregate is preferably 30% or less, more preferably 20% or less, even more preferably 10% or less, and even more preferably 5% or less. There is no lower limit to the degree of amorphization of the fine aggregate, but for example, it may be 0% or more, or 1% or more.

[0025] There are various methods for controlling the degree of amorphousness of fine aggregate, but generally, it is preferable to use a manufacturing method that rapidly cools the molten material. For example, there are methods such as melting the raw material and rapidly cooling it by blowing air through it, or processing it in a flame and rapidly cooling it. In any case, the cooling method can be appropriately selected at various rates depending on the material and particle size. It is also conceivable to amorphize a material that has already crystallized by heat treatment and cooling treatment. Among these, the flame melting method, in which heating and cooling can be easily controlled, is preferred.

[0026] The degree of amorphousness of the fine aggregate can be determined by the X-ray diffraction method shown below. Fine aggregate is crushed in a mortar and pressed onto the X-ray glass holder of a powder X-ray diffractometer for measurement. The powder X-ray diffractometer used is a MultiFlex manufactured by Rigaku Denki Co., Ltd. (light source: CuKα rays, tube voltage: 40kV, tube current: 40mA), and measurements are performed in the range of 2θ = 5 to 90° with a scanning interval of 0.01°, a scanning speed of 2° / min, and slits DS1, SS1, RS 0.3mm. In the range of 2θ = 10° to 50°, the X-ray intensities on the low and high angle sides are connected by straight lines, and the area below the line is defined as the background. The degree of crystallinity is determined using the software attached to the instrument, and subtracted from 100 to obtain the degree of amorphousness. Specifically, for the area above the background, amorphous peaks (halos) and each crystalline component are separated by curve fitting, the area of ​​each is determined, and the degree of amorphousness (%) is calculated using the following formula. Amorphization (%) = Area of ​​halo / (Area of ​​crystalline components + Area of ​​halo) × 100

[0027] The fine aggregate is preferably spherical in shape from the viewpoint of improving the fluidity of component (A). Here, spherical in shape according to this embodiment means a round shape like a ball, and more specifically, it means that the degree of sphericity is preferably 0.80 or higher, more preferably 0.85 or higher, even more preferably 0.90 or higher, even more preferably 0.95 or higher, and even more preferably 0.97 or higher. It is preferable from the viewpoint of the fluidity of the powdered hydraulic composition if the degree of sphericity of the fine aggregate according to this embodiment is above the above lower limit. Furthermore, it is also preferable from the viewpoint that the surface becomes smoother, and as a result the coating state of the inorganic binder layer becomes better. Furthermore, the upper limit for sphericity is specifically 1 or less. The sphericity of the fine aggregate can be measured in the same way as the sphericity of component (A).

[0028] From the viewpoint of handling the powdered hydraulic composition, the average particle size of the fine aggregate is preferably 0.1 mm or more, more preferably 0.5 mm or more, and from the viewpoint of handling the powdered hydraulic composition, preferably 5.0 mm or less, more preferably 2.0 mm or less, and even more preferably 1.0 mm or less. The average particle size of the fine aggregate can be measured in the same way as the average particle size of component (A).

[0029] Next, the inorganic binder layer of component (A) will be described. The metasilicate hydrate contained in the inorganic binder layer is an inorganic binder. Using metasilicate hydrate is preferable because it improves the crystallinity of the inorganic binder layer, and furthermore, component (A) becomes dry and has excellent room-temperature fluidity. In addition, by using metasilicate hydrate with a low melting point, the inorganic binder layer can be formed on the surface of the fine aggregate without dissolving it in water. In other words, since it is not necessary to use an aqueous solution of metasilicate hydrate in the process of manufacturing component (A), the step of removing water can be omitted, and the manufacturing method can be simplified.

[0030] From the above viewpoint, at least one selected from sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, potassium metasilicate pentahydrate, potassium metasilicate nonahydrate, and magnesium metasilicate pentahydrate is preferred as the metasilicate hydrate, and at least one selected from sodium metasilicate pentahydrate and sodium metasilicate nonahydrate is more preferred. The melting point of sodium metasilicate pentahydrate is 72°C, and the melting point of sodium metasilicate nonahydrate is 47°C.

[0031] The amount of the inorganic binder layer covering component (A) is, from the viewpoint of strength development of the hardened body of the hydraulic slurry, for example, 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, per 100 parts by mass of fine aggregate, and from the viewpoint of handling properties of the powdered hydraulic composition, for example, 10 parts by mass or less, preferably 8 parts by mass or less, and more preferably 6 parts by mass or less, per 100 parts by mass of fine aggregate (A).

[0032] The powdered hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (A) in amounts of, for example, 10 parts by mass or more, more 20 parts by mass or more, more 30 parts by mass or more, from the viewpoint of strength development of the hardened body of the hydraulic slurry, and 90 parts by mass or less, more 80 parts by mass or less, more 70 parts by mass or less, from the viewpoint of handling the powdered hydraulic composition.

[0033] Next, we will explain the alumina silica fine powder, which is component (B). (B) Examples of alumina silica fine powder include fine powder containing aluminosilicate (xM2O·yAl2O3·zSiO2·nH2O, where M is an alkali metal). Component (B) has the effect of eluting cations such as aluminum and silicon upon contact with an alkaline compound and / or an aqueous solution thereof, and acting as a source of these cations.

[0034] (B) The molar ratio of alumina (Al2O3) to silica (SiO2) of component (B) may be, from the viewpoint of strength development of the hardened product of the hydraulic slurry, for example, 0.05 or more, more specifically 0.10 or more, and 1.00 or less, and more specifically 0.50 or less in terms of alumina / silica.

[0035] Suitable examples of alumina silica fine powder for component (B) include: 1) industrial waste and by-products such as blast furnace slag fine powder, fly ash, clinker ash, fluidized bed coal ash, municipal solid waste incineration ash molten slag fine powder, red mud, and sewage sludge incineration ash molten slag fine powder; 2) natural aluminosilicate minerals such as metakaolin, clay and its ceramics; and 3) volcanic ash. Of these, the industrial waste described in 1) above is particularly suitable because, compared to the other components, it has no restrictions on its origin and contributes to the effective utilization of industrial waste resources.

[0036] (B) Component is preferably one or more selected from blast furnace slag fine powder and fly ash, from the viewpoint of strength development of the hardened body of the hydraulic slurry. Blast furnace slag powder is a by-product of iron refining in a blast furnace, and its main components are calcium oxide (CaO), silica (SiO2), and alumina (Al2O3). Its specifications are defined in JIS A 6206. In this invention, it is preferable to use blast furnace slag powder with a CaO content in the range of 30% by mass to 60% by mass. Fly ash is mainly composed of silica (SiO2) and alumina (Al2O3), and is classified into four types (I to IV) in JIS A 6201 based on particle size and flow value. JIS types I and II, which have fine particle size and high reactivity, are suitable. The CaO content in the fly ash may be 10.1% by mass or less.

[0037] (B) Component is the Blaine specific surface area (cm² 2The ratio ( / g) is, from the viewpoint of strength development of the hardened hydraulic slurry, for example, 1,500 or more, preferably 2,000 or more, more preferably 2,500 or more, even more preferably 3,000 or more, and even more preferably 3,500 or more. From the viewpoint of handling properties of the powdered hydraulic composition, it is, for example, 8,000 or less, preferably 7,500 or less, more preferably 7,000 or less, even more preferably 6,500 or less, and even more preferably 6,000 or less. The Blaine specific surface area of ​​component (B) is measured and calculated using a Blaine air permeability device specified in JIS R 5201.

[0038] The powdered hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (B) in amounts of, for example, 5 parts by mass or more, further 10 parts by mass or more, further 20 parts by mass or more, and 60 parts by mass or less, further 50 parts by mass or less, and further 40 parts by mass or less, from the viewpoint of strength development of the hardened body of the hydraulic slurry.

[0039] The powdered hydraulic composition of the present invention has a mass ratio (A) / (B) of the content of component (A) to the content of component (B), which can be, for example, 0.17 or more, more specifically 0.50 or more, more specifically 1.0 or more, and then 18 or less, more specifically 10 or less, and more specifically 5 or less, from the viewpoint of strength development of the hardened hydraulic slurry.

[0040] The powdered hydraulic composition of the present invention preferably contains component (A) and component (B) in total at 90 parts by mass or more, more specifically 95 parts by mass or more, and 100 parts by mass or less, per 100 parts by mass of the composition, with the total being 100 parts by mass, i.e., the powdered hydraulic composition of the present invention may consist of component (A) and component (B).

[0041] The powdered hydraulic composition of the present invention may contain any components other than components (A) and (B). Examples of optional components include water-reducing agents, air-entraining agents, fluidizing agents, hardening accelerators (alkaline stimulants), defoaming agents, rapid setting agents, shrinkage reducing agents, hardening retarders, and rust inhibitors. The powdered hydraulic composition of the present invention may contain one or more of these optional components.

[0042] The powdered hydraulic composition of the present invention may optionally contain cement, but care must be taken with its content as cement affects the initial hardening rate. Furthermore, from the viewpoint of providing a powdered hydraulic composition with reduced cement content, a lower cement content is preferable. The powdered hydraulic composition of the present invention may optionally contain cement, and the cement content may be less than 30 parts by mass, more preferably 20 parts by mass or less, more preferably 10 parts by mass or less, or more preferably 1 part by mass or less, per 100 parts by mass of component (B), and may also contain 0 parts by mass, i.e., no cement at all. Here, examples of cement include Portland cement, white Portland cement, blended cement, eco-cement, alumina cement, ultrafast-setting cement, grout cement, oil well cement, etc. The Portland cement content of the powdered hydraulic composition of the present invention may be within the above range relative to component (B).

[0043] The powdered hydraulic composition of the present invention is suitable as a composition for geopolymer formation. For example, by mixing the powdered hydraulic composition of the present invention with water, a hydraulic slurry is obtained, and by curing this hydraulic slurry, a geopolymer is formed and a cured body is obtained. The powdered hydraulic composition of the present invention may be a so-called premix, and may further be a premix for geopolymers.

[0044] <Method for manufacturing powdered hydraulic composition> The present invention comprises the steps of (1) mixing metasilicate hydrate and fine aggregate at a temperature above the melting point of the metasilicate hydrate to obtain a mixture, Step (2) is to cool the mixture to a temperature below the melting point of the metasilicate hydrate to obtain a coated fine aggregate having (A) fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate [hereinafter referred to as component (A)], (3) is a step of mixing component (A) and (B) alumina silica fine powder [hereinafter referred to as component (B)], This invention relates to a method for producing a powdered hydraulic composition containing [a specific substance].

[0045] The method for producing the powdered hydraulic composition of the present invention may appropriately apply the matters described in the description of the powdered hydraulic composition of the present invention. Specific examples and preferred examples of components (A) and (B) in the method for producing the powdered hydraulic composition of the present invention are the same as those for the powdered hydraulic composition of the present invention. The method for producing the powdered hydraulic composition of the present invention is suitable as a method for producing the powdered hydraulic composition of the present invention.

[0046] In step (1), the metasilicate hydrate and fine aggregate are mixed at a temperature above the melting point of the metasilicate hydrate, so that the surface of the fine aggregate is coated with the fluidized metasilicate hydrate. Methods for mixing metasilicate hydrate at a temperature above its melting point include, for example, adding metasilicate hydrate to fine aggregate heated to a temperature above its melting point and mixing the fine aggregate and metasilicate hydrate while melting the metasilicate hydrate [Step (1A)], and adding heated and melted metasilicate hydrate to fine aggregate and mixing [Step (1B)]. From the viewpoint of shortening the time required for coating, Step (1B) is preferred.

[0047] From a similar viewpoint, it is preferable in step (1) to mix the metasilicate hydrate without first preparing it as an aqueous solution. Furthermore, it is preferable that step (1) does not include a step in which water is intentionally added.

[0048] The mixing conditions, such as the stirring speed and processing time, when mixing fine aggregate and metasilicate hydrate can be appropriately determined depending on the amount of mixture being processed.

[0049] In step (2), the mixture obtained in step (1) is cooled to a temperature below the melting point of the metasilicate hydrate, thereby reducing the fluidity of the metasilicate hydrate and fixing it to the surface of the fine aggregate, thereby forming a metasilicate hydrate layer, i.e., an inorganic binder layer. This yields a coated fine aggregate [component (A)] having fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate.

[0050] In step (3), component (A) obtained in step (2) is mixed with the alumina silica fine powder of component (B). The method, apparatus, and conditions for mixing component (A) and component (B) are not particularly limited, and those suitable for mixing the powder components can be appropriately selected.

[0051] <Hydraulic slurry> The present invention relates to a hydraulic slurry obtained by compounding the powdered hydraulic composition of the present invention with water. From the viewpoint of the fluidity of the hardened hydraulic slurry, water can be added in an amount of, for example, 1 part by mass or more, further 5 parts by mass or more, further 10 parts by mass or more, per 100 parts by mass of the powdered hydraulic composition of the present invention. From the viewpoint of the strength development of the hardened hydraulic slurry, water can be added in an amount of 50 parts by mass or less, further 35 parts by mass or less, further 20 parts by mass or less.

[0052] The hydraulic slurry of the present invention is suitable as a slurry for geopolymer formation. By curing the hydraulic slurry of the present invention, a geopolymer is formed and becomes a cured body. The hydraulic slurry of the present invention may be a slurry for geopolymers.

[0053] <Method for manufacturing a hardened body> The present invention comprises the steps of (I) mixing the powdered hydraulic composition of the present invention with water to obtain a hydraulic slurry, (II) A step of curing the hydraulic slurry to obtain a hardened body, This relates to a method for producing a cured body, including the following:

[0054] In step (I), water can be mixed in an amount of, for example, 1 part by mass or more, further 5 parts by mass or more, and further 10 parts by mass or more, per 100 parts by mass of the powdered hydraulic composition of the present invention, from the viewpoint of the fluidity of the hardened hydraulic slurry, and from the viewpoint of the strength development of the hardened hydraulic slurry, 50 parts by mass or less, further 35 parts by mass or less, and further 20 parts by mass or less.

[0055] The method, apparatus, and conditions for mixing the powdered hydraulic composition of the present invention with water in step (1) are not particularly limited, and suitable methods, apparatus, and conditions can be appropriately selected for slurry preparation.

[0056] In step (II), the hydraulic slurry obtained in step (I) is cured to obtain a cured body. The curing in step (II) can be carried out under general conditions for obtaining a cured geopolymer. In step (II), the curing temperature can be, for example, 20°C or higher, further 30°C or higher, further 40°C or higher, and then 80°C or lower, and further 70°C or lower. In addition, the curing time in step (II) can be, for example, 1 hour or more and 28 days or less.

[0057] <Additive for powdered hydraulic composition> The present invention relates to an additive for powdered hydraulic compositions, comprising a coated fine aggregate [component (A)] having fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate. The additive for powdered hydraulic composition of the present invention may be appropriately adapted to the matters described in the description of the powdered hydraulic composition of the present invention. Specific examples and preferred examples of component (A) in the additive for powdered hydraulic composition of the present invention are the same as those for the powdered hydraulic composition of the present invention. The powdered hydraulic composition additive of the present invention is an additive used in powdered hydraulic compositions. The powdered hydraulic composition additive of the present invention may be an additive used in powder compositions for the formation of geopolymers. The powdered hydraulic composition additive of the present invention may be an additive consisting of component (A). [Examples]

[0058] The components used in the examples and comparative examples are shown below. • Fine aggregate: Mountain sand (from Joyo, Kyoto City; surface-dry specific gravity 2.54, coarseness ratio 2.73, amorphism 1.1%, sphericity 0.86, average particle size 0.6 mm, oven-dried) • Inorganic binder 1: Sodium metasilicate 9-hydrate (melting point 48°C, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) • Inorganic binder 2: Sodium metasilicate pentahydrate (melting point 72°C, manufactured by Sigma-Aldrich Co. LLC) • Alumina silica fine powder 1: Blast furnace slag fine powder (Brain specific surface area: 4,200 cm²) 2 ( / g, alumina / silica molar ratio = 0.25) • Alumina silica fine powder 2: Fly ash (JIS Class II, Blaine specific surface area: 3,500 cm²) 2 ( / g, alumina / silica molar ratio = 0.26) • Tap water (Wakayama City tap water)

[0059] <Example 1 and Comparative Example 1> (1) Preparation of coated fine aggregate (Example) The inorganic binder described above was heated in a water bath (80°C for 1 hour) to obtain a melt. Next, fine aggregate (80°C) that had been heated to a completely dry state was added to a Hobart mixer as described in JIS R 5201, and stirring was started at 140 rpm. The melted inorganic binder was then added to the mixture so that the composition in the hydraulic slurry was in parts by mass as shown in Table 1, and the mixture was kneaded at 140 rpm for 5 minutes. After that, it was allowed to cool naturally to room temperature (20°C), and coated fine aggregate with the inorganic binder layer of the present invention formed on its surface was obtained with a yield of 99.3%. At this time, the coated fine aggregate with the inorganic binder layer formed on its surface had an angle of repose of 33.6°, a sphericity of 0.88, and an average particle size of 0.6 mm.

[0060] (2) Preparation of powdered hydraulic composition (premix) The coated fine aggregate and alumina silica fine powder obtained in (1) were added to a Hobart mixer described in JIS R 5201 in such a way that the composition of the hydraulic slurry was in parts by mass as shown in Table 1, and mixed at 140 rpm for 20 seconds to prepare the powder hydraulic composition (premix) of the example. In the comparative example, without using coated fine aggregate, fine aggregate adjusted to an extremely dry state, an inorganic binder, and alumina silica fine powder were each added independently to the hydraulic slurry in the parts by mass shown in Table 1, and the mixture was mixed at 140 rpm for 20 seconds to prepare a powder hydraulic composition (premix).

[0061] (3) Preparation of hydraulic slurry and its cured form The powdered hydraulic composition (premix) prepared in (2) and tap water were added in the parts by mass shown in Table 1 to a Hobart mixer described in JIS R 5201 and mixed at 140 rpm for 180 seconds to prepare a hydraulic slurry. Next, using the hydraulic slurry immediately after preparation, mortar specimens of φ5 × 10 cm were prepared in accordance with JSCE-F 506. After curing at 20°C for 7 days, the specimens were removed from their molds, and a compressive strength test was conducted in accordance with JSCE-G 505. The uniaxial compressive strength (N / mm²) was calculated as the average value for n=2. 2 ) was recorded. The results are shown in Table 1.

[0062] <Example 2 and Comparative Example 2> Powdered hydraulic compositions (premixes) were prepared in the same manner as in Example 1 and Comparative Example 1, except that the components and parts by mass were changed as shown in Table 1, and the uniaxial compressive strength was measured. The results are shown in Table 1.

[0063] [Table 1]

[0064] In Table 1, Examples 1 and 2 showed superior strength development compared to Comparative Examples 1 and 2. This is thought to be because the inorganic binder containing metasilicate hydrate permeated the porous structure of the fine aggregate, increasing the contact surface area between the inorganic binder and the fine aggregate. During the hardening process, the inorganic binder and the fine aggregate bonded more strongly, improving the strength of the hardened material.

[0065] <Example 3, Comparative Example 3, and Reference Example 3> (1) Measurement of the angle of repose The angles of repose were measured for the powder hydraulic compositions of Example 1 and Comparative Example 1, as well as the components used in their preparation. Specifically, the angles of repose for (a) the powder hydraulic composition (premix) of Example 1, (b) the powder hydraulic composition (premix) of Comparative Example 1, (c) uncoated fine aggregate, (d) coated fine aggregate obtained using inorganic binder 1, (e) inorganic binder 1, (f) alumina silica fine powder 1, and (g) alumina silica fine powder 2 were measured using an angle of repose meter ASK-01 (manufactured by AS ONE Corporation). The results are shown in Table 2.

[0066] [Table 2]

[0067] In Table 2, the powder hydraulic composition of Example 1 (Example 3-1) showed a smaller angle of repose, i.e., superior powder fluidity, compared to the powder hydraulic composition of Comparative Example 1 (Comparative Example 3-1). This is thought to be because the inorganic binder containing bound water permeated into the porous structure of the fine aggregate, suppressing the decrease in fluidity due to liquid crosslinking between powder particles. This is also suggested by the fact that the angle of repose of uncoated fine aggregate only (Reference Example 3-1) was about the same as that of coated fine aggregate with a layer of inorganic binder 1 formed on its surface (Reference Example 3-2), and the angle of repose of inorganic binder 1 (Reference Example 3-3) was larger than that of these fine aggregates. Both Example 3-1 and Comparative Example 3-1 were evaluated using powdered hydraulic compositions prepared with the same amounts of the components from Reference Examples 3-1, 3-3, and 3-5. However, the angle of repose was smaller in Example 3-1, indicating that incorporating it in the form of coated fine aggregate (Reference Example 3-2) leads to improved fluidity.

Claims

1. A powdered hydraulic composition comprising: (A) a coated fine aggregate having fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate [hereinafter referred to as component (A)]; and (B) an alumina-silica fine powder [hereinafter referred to as component (B)].

2. 2. The powdery hydraulic composition according to claim 1, wherein the metasilicate hydrate is at least one selected from the group consisting of sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.

3. 3. The powdery hydraulic composition according to claim 1 or 2, which optionally contains cement, and the content of the cement is less than 30 parts by mass per 100 parts by mass of the component (B).

4. (1) mixing a metasilicate hydrate and a fine aggregate at a temperature equal to or higher than the melting point of the metasilicate hydrate to obtain a mixture; (2) cooling the mixture to a temperature below the melting point of the metasilicate hydrate to obtain (A) a coated fine aggregate having a fine aggregate and an inorganic binder layer containing the metasilicate hydrate formed on the surface of the fine aggregate (hereinafter referred to as component (A)); (3) mixing the component (A) with the fine alumina-silica powder (B); A method for producing a powdery hydraulic composition comprising the steps of:

5. A hydraulic slurry comprising (A) a coated fine aggregate having fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate [hereinafter referred to as component (A)], and (B) a powdered hydraulic composition containing an alumina-silica fine powder [hereinafter referred to as component (B)], mixed with water.

6. The hydraulic slurry according to claim 5, wherein the metasilicate hydrate is one or more selected from sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.

7. A hydraulic slurry as described in claim 5 or 6, optionally containing cement, wherein the cement content is less than 30 parts by mass per 100 parts by mass of component (B).

8. A process (I) for obtaining a hydraulic slurry by mixing water with a powdered hydraulic composition including (A) a coated fine aggregate having a fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate (hereinafter referred to as component (A)), and (B) an alumina-silica fine powder (hereinafter referred to as component (B)); A step (II) of curing the hydraulic slurry to obtain a hardened body; A method for producing a cured body, comprising:

9. A method for producing a hardened body as described in claim 8, wherein the metasilicate hydrate is one or more selected from sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.

10. A method for producing a hardened body as described in claim 8 or 9, optionally containing cement, wherein the cement content is less than 30 parts by mass per 100 parts by mass of component (B).

11. A powdered additive for hydraulic compositions comprising a coated fine aggregate having a fine aggregate and an inorganic binder layer containing metasilicate hydrate formed on the surface of the fine aggregate.